Формування конкурентних переваг виробників ігристих вин - Закревська, Людмила Миколаївна (My University, 2019)
Стаття присвячена проблемам формування конкурентних переваг виробників ігристих вин. Обґрунтовано, що основними генераторами формування конкурентних переваг суб’єктів господарювання виступають споживачі, які хочуть отримати товар вищої якості або/та за доступною ціною. Оцінювання конкурентних переваг можна здійснювати за рядом критеріїв, які доцільно поділити на зовнішні (визначаються ендогенними аспектами діяльності підприємства) і внутрішні (базуються на можливості створити необхідні цінності для споживачів). The article is devoted to the problems of forming the competitive advantages of sparkling wine producers. The main generators of the formation of competitive advantages of business entities are consumers. They want to get higher quality goods and / or at an affordable price. The evaluation of competitive advantages can be carried out according to the criteria. It is expedient to divide them into external and internal ones. External competitive advantages are determined by the endogenous aspects of the enterprise's activity. Internal competitive advantages are based on the ability to create the necessary values for consumers.
Keywords: кафедра економіки і права; конкуренція; competition; конкурентні переваги; competitive advantages; конкурентоспроможність; competitiveness; конкурентні можливості; competitive opportunities